Functional relationships and productivity factors of the fine aroma cocoa production system - Martínez, Julia; Urdaneta, Fátima; Peña, María; Casanova†, Ángel (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
In the South of Lake Maracaibo, fine aroma cocoa production systems (FACPS) have been developed where good quality beans are produced, but with low yields; this situation can beassociated with multiple social, technical and economic factors, whose interrelationships require a comprehensive analysis to be able to identify their limitations and potentialities. This research was proposed with the objective of explaining how the functional relationships of the FACPS affect its productivity, as well as weighing the productive factors. A sample of 84 producers from the South of Lake Maracaibo was taken. Data were analyzed by Cluster analysis to group the production units by their functional similarities according to four calculated indices: Agronomic Practices Index (API), Labor Force Index (LFI), Production Means Index (PMI) and Socioeconomic Environment Index (SEI), then an analysis of variance was performed to establish the productivity differences between groups. The factors weighting was carried out by a logistic regression model. Results showed the formation of four functional groups with their arrangement of components and relationships. Productivity indicators were significantly different (p ≤ 0.05) among groups, this indicates that the way the system’s components are arranged affects its productive outputs. The logistic regression model indicated that the educational level, the low percentage of flat surface and the farm size are the main factors that increase the probability that a production unit belongs to the group with the highest yields.